Franklin D. Roosevelt papers - Roosevelt, Franklin D. (Franklin Delano), 1882-1945.
Original letters from Roosevelt to Herb E. Sharp, 1932, and Sharp to Roosevelt, 1933; photocopies of letters to Roosevelt from William G. McAdoo, 1933, and Frank Murphy, 1939; speeches and proclamations (1933-1944); signed copy of prayer read on D-Day (June 6, 1944); teletype sheets regarding the death of Roosevelt; and various clippings and memorabilia (1934-1946) relating to Roosevelt and his family.
Microfilm edition of Herb E. Sharp letters available
In part, photocopies.
U.S. president.
Keywords: McAdoo, W. G. -- 1863-1941 -- Correspondence; Murphy, Frank, -- 1890-1949 -- Correspondence; Sharp, Herb E. -- Correspondence; Roosevelt family; United States -- Politics and government -- 1933-1945.; Presidents -- United States